1855 Laws and Gen. Ordinances of the City of Dayton 214, An ordinance for the punishment of offenses, § 38 - (:unkn) unknown (General Publisher, 1855)
If any person, or persons, shall fire any cannon, gun, or other firearms, within the bounds of the building lots, or cemetery ground in this city, or within one hundred yards of any public road, within this corporation, except by permission of council, and except in proper situations for firing salutes, or by command of a military officer in performance of military duty, every person, so offending, on conviction thereof, shall pay a fine not exceeding ten dollars, and costs.
--
Keywords: DISCHARGE